Unintended Consequences of Money-Laundering Regulations - Fabrizio Colella; Keith Maskus; Alessandro Peri (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
Tighter money-laundering regulations in offshore financial havens may inadvertently spur incentives to launder money domestically. Our study exploits regulations targeting financially based money laundering in Caribbean jurisdictions to uncover the creation of front companies in the United States. We find that counties exposed via offshore financial links to these jurisdictions experienced an increase in business activities after the tightening of anti-money-laundering regulations. The effect is more pronounced among small firms, in sectors at high risk of money laundering, and in regions with high intensities of drug trafficking. Our work provides the first empirical evidence of the real effects of policy-induced money-laundering leakage.
Keywords: F30; K40; G28; H00; D58; 330; Money laundering; money-laundering leakage; business establishments; offshore leaks; regulatory reforms; monopolistic competition